Health Promotion on the Behavior of Women of Childbearing Age in Early Detection Examinations for Cervical Cancer at Makassar City Health Centers - Wahyuni, Ria; Amalia, Rizki; Supriatin, Supriatin; Kurniasih, Uun; Treasa, Adisty Dwi; Reffita, Lea Ingne; Ambarwati, Eny Retna; Werdyaningsih, Endang (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The Influence of Health Education on Women's Age Behavior in IVA Examinations in Early Detection of Cervical Cancer at Community Health Centers in Makassar. Currently, the coverage of early detection of cervical cancer is still very low, this is due to a lack of public knowledge and awareness to participate in early detection programs for cervical cancer. IVA examination is an early detection program for cervical cancer implemented by the government. The aim of this research was to determine the influence of health education on the behavior of women of childbearing age in early detection of cervical cancer at the IVA examination at the Community Health Center in Makassar. The research design used was a quasi-experimental pre-post design with a comparison group that attempted to reveal the effectiveness of the independent variable on the dependent variable by stretching the control group in addition to the experimental group with a sample size of 66 women of childbearing age. The results of the research show that health education influences the knowledge, attitudes and actions of women of childbearing age in IVA examinations at early detection of cervical cancer at Community Health Centers in Makassar, from the T-Test statistical test p sig = 0.000 < 0.05. Health education in IVA examinations in early detection of cervical cancer has the effect of increasing knowledge, attitudes and actions to be more positive, it is hoped that the authorized agencies can carry it out with a wider reach and better quality.